Global environmental impact of informal settlements and perceptions of local environmental threats: An empirical case study in Suva, Fiji. (November 2017) - Devi, Poonam P.; Lowry, John H.; Weber, Eberhard
Abstract: It is commonly expected that informal settlements in developing countries have a smaller ecological footprint than more economically advantaged areas because they consume fewer resources and use less energy. In this paper we examine this idea by comparing material consumption of two informal settlements to one moderate socio-economic status (SES) neighbourhood in Suva, Fiji. We use the concept of the Ecological Footprint (EF) as a metric of comparison. Using a component-based EF approach we administered a questionnaire to 150 respondents from two informal settlements and one adjacent planned neighbourhood. Total EF and separate EF components (water, food, transport, energy, clothing, and material assets) were analysed through graphs, by examination of descriptive statistics, and through the use of non-parametric inferential statistics. We found differences between the adjacent planned neighbourhood and the informal settlements for several EF components, but found no difference for other EF components (e.g. water consumption). Through questionnaires and interviews we also examined perceived level of concern for environmental threats of informal settlement dwellers and residents of an adjacent moderate SES neighbourhood who share the same geographic space, but have very different living conditions. We found that concerns about sewage, deforestation, clean water and poor sanitation were of particularly high concern in one informal settlement, but not the other, suggesting that perceptions of threat can be very different even among informal settlements. We conclude that a better understanding of the social characteristics of informal settlements is valuable for informal settlement urban planning decisions in developing countries.